Farm-to-fork… and beyond? A call to incorporate food waste into food systems research. Issue 1 (2nd January 2020) - Hodgins, Kelly; Parizeau, Kate
Abstract: Although food waste is gaining attention as an issue of environmental, social, and economic concern, this topic has only been taken up minimally by food scholars, despite its apparent relevance to food systems scholarship. Through a literature scan of nine food systems journals, we identify and characterize all instances of "food waste" and "food loss" mentions. We find that reference to this important topic is growing within food studies but is still a marginal concept. To help advance the discourse on food wastage, we suggest three potential areas of food systems research that could extend the scholarship, particularly drawing from analytical developments in discard studies. We encourage food studies scholars to consider waste as an intrinsic element of the food systems they study and as a fruitful boundary topic for future research.